Roadmap for sustainable aviation abiofueles for brazil - Cortez, Luís Augusto Barbosa (2014)
The aviation industry is committed to reducing its environmental impact and has established the ambitious goals to reach carbon neutral growth by 2020 and to reduce carbon dioxide emissions by 50% (from 2005 levels) by 2050. BOEING and EMBRAER. as leading aviation companies committed to a more sustainable future. have joined efforts to support initiatives to lower greenhouse gas (GHG) emissions derived from air transportation. Brazil is internationally recognized for its long experience of using biomass for energy purposes. beginning with wood. sugarcane ethanol. and biodiesel. Modern bioenergy represents around 30% of the Brazilian energy matrix. and has a long track record reconciling biofuel production. food security and rural development. In this context. BOEING. EMBRAER. UNICAMP and FAPESP initiated this project to conduct a national assessment of the technological. economic and sustainability challenges and opportunities associated with the development and commercialization of sustainable biofuel for aviation in Brazil. The result of this effort is the book "Roadmap for Sustainable Aviation Biofuels for Brazil - Flightpath to Aviation Biofuels in Brazil". The development of this new industry will entail the participation of different sectors of the Brazilian economy and will position the country as a key player with a unique strategic advantage worldwide